AB1356-HPR GOUT IN SPANISH PRIMARY HEALHCARE CENTERS: STILL A LONG WAY TO GO. (2nd June 2020) - Pou, M. A.; Jeria, S.; Prada-Ojeda, A.; Ferrer, S.; García-Guillén, A.; Corominas, H.; Diaz Torne, C.
Abstract : Background: Gout has a prevalence >2.5% in the Spanish adult population. It is a chronic disease that without proper treatment causes pain, joint deformity and increased cardiovascular risk and mortality. Recent advances have demonstrated that if correctly treated the disease can be controlled and even 'cured'. Most gouty patients are diagnosed and treated by general practitioners (GPs). There is evidence that the management if these patients is not good neither at Rheumatology Units nor at Primary Healthcare (PHC) centers.Several causes of this mismanagement can be found in the literature. Objectives: Design and evaluation of the results of a questionnaire created from a bibliographic search focused on areas of improvement of gout management in PHC. Methods: A search was made in Pubmed to identify the main barriers described in the management of patients with gout in primary care. The terms used were: "Gout", "primary healthcare" and "education". A Google Form of gout knowledge and management questionnaire was designed, taking into account what is described in the literature. The Google Form was sent to all GP from an urban area via mail and to other contacts via WhatsApp and twitter. Results: Responses were obtained from 224 GPs; 69.5% were women; 73.1% had between 11 and 30 years of professional experience; 96.4% answered that gouty are mostly controlled in primary care; 99.6% performs the diagnosis of gout without analysis of synovial fluid and 17% diagnosed only by clinics without urate levels; 55.9% of GPs do not use any reference guide. Of those who use, the 73% use GUIPCLINGOT and 40% use SEMGs one; 80.5% have not done any gout course in the last 5 years; 26% did not have access to a rheumatologist to confirm the gout diagnosis; only 30.8% knew the therapeutic objective of the urate lowering therapy (ULT); 28.6% considered the beginning of ULT after the first attack; 62% believed that the most important part of the treatment was changing diet and lifestyles; 88.8% did not perform any specific education for these patients by the nurse; just 37.2% carried out a treat-to-target strategy to lower urate levels. Conclusion: The questionnaire identifies multiple points of improvement for the management of this pathology in accordance with the described in the literature. Most GPs are unaware of the therapeutic objective of the ULT. Disclosure of Interests: None declared